Human errors is continuous risky in construction industry: is it because of negligence or lack of knowledge? Kesalahan manusia terus menerus berisiko dalam industri konstruksi: apakah karena kelalaian atau kurangnya pengetahuan? - Aziz Zikriyoev (Academia Open, 2019)
Why is human capital relevance in organizations? It is because of relations are essential for hiring, managing, training and retaining talented and high performing employees. Human Capital plays an important role in the recruitment process in all sectors of the economy. Especially in construction it is obligatory obey all requested rules and regulations due to extreme risk of getting injured or fatal death. In some cases lack of attention and knowledge workers face various types’ accidents on site. In this paper work it is studied cause and effects of low safety regulation and working requirements during working hours. As for the world experiences in Uzbekistan also major problems in this concern. According to the survey analysis construction sector employees had been studied of safety enforcement. Main purpose of the current paper is examine risk level on site, evaluate human factor and preventing accident rate by reducing workers knowledge and experience for self-awareness.